Visuality and Spectacle: approaches and historical connections (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article resulted from the investigation of approaches to visuality, considering genesis, references and introduction to the knowledge produced in this context, considering probable approximations with the spectacle. The investigation indicated theoretical connections in Visual Culture leading to Cultural Studies that have been ongoing in England since the 1950s and incorporated several authors, from Michael Baxandall to Nicholas Mirzoeff, including Hal Foster and Tom Mitchel. The research suggested that the notion of visuality be treated within the assumptions of academic-scientific research.
Keywords: visuality; spectacle; visual culture; thought and images; vision